Circular Economy and Integrated Pest Management in Rice Farming: A Model for Sustainable Agricultural Education - Rita Parmawati; Soemarno; Setyo Widagdo; Indra Purnama Putra (Postgraduate, University of Mataram, 2025)
This study aims to develop a circular economy model to promote the sustainability of Integrated Pest Management (IPM)-based rice farming in Kediri Regency, Indonesia. Agricultural systems in the region face persistent challenges, including environmental degradation and chemical overuse. By adopting key principles of the circular economy—such as reduce and recycle—this research offers a practical solution to optimize resources and minimize ecological impact in rice farming systems. A mixed-methods approach was employed, combining sustainability assessment tools and structural equation modeling to evaluate and validate the model. Data were collected from 100 purposively selected IPM-oriented farmer groups. The results indicate that the